EXERCISE CAPACITY IN PATIENTS WITH CORONARY HEART DISEASE AND PERIPHERAL ARTERY DISEASE, RECEIVING LONG-TERM MILDRONATE THERAPY - V. Ya. Dzerve; Yu. M. Pozdnyakov (Российский кардиологический журнал)
The paper presents the results of 3 prospective, randomised, double-blind, placebo-controlled trials of patients with coronary heart disease (CHD) and peripheral artery disease (PAD). The aim was to compare veloergometry parameters and skeletal muscle strength in CAD patients, as well as exercise capacity dynamics in PAD patients, during long-term standard therapy with or without additional administration of mildronate (M). According to 3- and 12-month results for CAD patients, M groups demonstrated substantial increases in veloergometry exercise duration and maximal workload, as well as skeletal muscle strength, compared to placebo groups. In PAD patients, 24-week M therapy was associated with substantial increase in absolute claudication distance (ACD) during treadmill test, compared to placebo. Long-term M therapy was effective and safe. Positive effects on ACD were observed even one month after the end of M treatment.